Modern languages : learning and teaching in an intercultural field - Phipps, Alison M. (Teaching & learning the humanities in higher education., 2004)
Modern Languages is written by teachers of modern languages and tackles the specifics of the discipline while situating it within the literature on teaching Modern Languages in Higher Education. Drawing on data and learning experiences from students of modern languages, the authors identify key problems for teachers and learners and provide examples of critical incidents, which point to generic as well as specific difficulties in teaching modern languages.